2013
DOI: 10.1111/iju.12235
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal onlay (Barbagli technique) versus dorsal inlay (Asopa technique) buccal mucosal graft urethroplasty for anterior urethral stricture: A prospective randomized study

Abstract: Objective: To compare both the dorsal onlay technique of Barbagli and the dorsal inlay technique of Asopa for the management of long anterior urethral stricture. Methods: From January 2010 to May 2012, a total of 47 patients with long anterior urethral strictures were randomized into two groups. The first group included 25 patients who were managed by dorsal onlay buccal mucosal graft urethroplasty. The second group included 22 patients who were managed by dorsal inlay buccal mucosal graft urethroplasty. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 26 publications
(25 reference statements)
2
16
0
1
Order By: Relevance
“…The harvest site was routinely (4.0 monofilament interrupted sutures) closed. One‐stage bulbar redo BMGU was performed using the ventral‐onlay technique for bulbar and the dorsal inlay technique for penile recurrent strictures, as described previously for initial BMGU . A transurethral and a suprapubic catheter were placed intra‐operatively.…”
Section: Methodsmentioning
confidence: 99%
“…The harvest site was routinely (4.0 monofilament interrupted sutures) closed. One‐stage bulbar redo BMGU was performed using the ventral‐onlay technique for bulbar and the dorsal inlay technique for penile recurrent strictures, as described previously for initial BMGU . A transurethral and a suprapubic catheter were placed intra‐operatively.…”
Section: Methodsmentioning
confidence: 99%
“…Aldaqadossi et al [13] also reported that dorsal onlay and dorsal inlay urethroplasties provide similar success rates, but the onlay technique is harder to perform, has a longer operative time and more blood loss and is associated with more complications. Second, while the urethra is widened, more covering tissue is required, and sometimes we need to transfer scrotal tissue to cover the wounds of the ventral side.…”
Section: Discussionmentioning
confidence: 99%
“…The approach also requires less extensive exposure of the spongy tissue, less bleeding from the corpus spongiosum, and less mechanical damage to the graft [20-22]. The dorsal onlay technique of Barbagli and the dorsal inlay technique of Asopa buccal mucosal graft urethroplasty provide similar success rates, but the Asopa technique is easy to carry out, provides shorter operative time and less blood loss, and it is associated with fewer complications for anterior urethral stricture repair [23]. …”
Section: Discussionmentioning
confidence: 99%